Cementing techniques for hip resurfacing arthroplasty: in vitro study of pressure and temperature - Bitsch, Rudi G.; Loidolt, Travis; Heisel, Jens Christian; Schmalzried, Thomas P. (The journal of arthroplasty, 2011)
Cementing irregularities have been associated with femoral failures of resurfacing arthroplasties in retrieval studies. We used an in vitro model to measure pressure, temperatures, and cement penetration as a function of 6 different cementing techniques. Filling the component with cement can lead to overpenetration or increase the resistance to component seating with resultant polar cement mass. Both conditions result in high and long-lasting cement pressures, cement defects, as well as peak temperatures higher than 50°C. Manual application of cement provides complete penetration of the available fixation area with the lowest cement pressures, the smallest total cement mass, and a peak temperature of 36.0°C ± 4.1°C. Application of the principles elucidated by this study may reduce the risk of cement overpenetration and incomplete seating.
Gesehen am 30.03.2022
First published online: 22 January 2010